Effect of soy flour addition and heatprocessing method on nutritional quality and consumer acceptability of cassava complementary porridges - Muoki, Penina Ngusye; Kock, H.L. de; Emmambux, M.N. (Wiley, 2012)
BACKGROUND: The nutritional quality of cassava complementary porridge was improved through extrusion cooking and compositing with either defatted or full fat soy flour (65:35 w/w), and product acceptability by mothers with children of the target population was evaluated.